Evaluating a Novel Learning Intervention Grounded in the Education for Environmental Citizenship Pedagogical Approach: A Case Study from Cyprus - Hadjichambis, Andreas Ch.; Paraskeva-Hadjichambi, Demetra; Georgiou, Yiannis (My University, 2022)
In times of environmental crisis, Education for Environmental Citizenship (EEC) is argued to be of great significance in the development of secondary education students’ pro-environmentalism as environmental citizens. However, given that EEC is still emerging, there is a lack of empirical foundation on how environmental citizenship can be approached in a pedagogically sound way; as a result, empirical documented interventions in secondary education are also limited. This paper presents a case study from Cyprus, which evaluates the impact of a novel learning intervention grounded in the EEC pedagogical approach, taking into consideration the potential effect of students’ gender as well as of their past/present EC actions. The participants were fifty students (n = 50) in secondary biology education who attended the learning intervention; the students comprised 29 girls (58%) and 21 boys (42%), from two intact classrooms. Data were collected with the Environmental Citizenship Questionnaire (ECQ), which was administered before (pre-) and after (post-) the learning intervention, and were analyzed using a combination of non-parametric statistical analyses (Wilcoxon signed-rank test, Mann–Whitney U test, Spearman’s Correlation and cluster analysis). Our findings indicated that there was a statistically significant increase in the students’ EC learning gains, both EC competences and EC future actions, by the end of the intervention. However, our findings also indicated that the impact of the learning intervention was related significantly to the students’ gender as well as to their past/present EC actions, as these were reported by the students prior the intervention. Overall, our findings provide empirical substantiation of the contribution of the EEC pedagogical approach to the development of secondary students’ EC. At the same time, our study also pointed out the critical roles of gender and past/present EC actions in students’ learning gains.
Keywords: Education for Environmental Citizenship (EEC); EEC pedagogical approach; Environmental Citizenship Questionnaire (ECQ); Gender; Learning intervention; Past/present EC actions